Self-Strengthening Bio-based Coatings via Autoxidative Cross-linking of Linseed Oil-Derived Surfactants - Ri Myong Kim; Hyon Tae Pak; Son Il Hong; Song Hun Kang; Song Ik Jo; Su Jin Ju; Yong Hwan Han; Il Song Liang (UPT Laboratorium Terpadu, Universitas Diponegoro, 2026)
A high-performance, bio-based wax emulsion was formulated using surfactants derived from linseed oil—linseed oil sodium soap (LOS) and linseed oil monoglyceride (LOM). Based on their complementary hydrophilic-lipophilic balance (HLB 18 for LOS, 5 for LOM), a 50:50 blend was predicted to match the HLB requirement of beeswax (9–12). Experimental optimization confirmed that a 15% beeswax emulsion stabilized by 5% total concentration of this blend exhibited exceptional properties: fine particle size (D[4,3] = 307 nm), high electrostatic stability (ζ = -31.7 mV), and resistance to centrifugation and thermal aging (50 °C, >28 days). The key innovation lies in the dry film performance. Quantitative FTIR analysis revealed a 72% consumption of C=C bonds over 30 days, confirming spontaneous oxidative crosslinking of the surfactants' unsaturated bonds. This crosslinking led to a continuous 59% increase in elastic modulus (255 → 405 MPa) and superior water resistance (0.9% absorption), significantly outperforming films prepared with conventional saturated or synthetic emulsifiers. This work demonstrates that linseed oil-derived surfactants function as dual-purpose agents, effective emulsifiers and latent crosslinkers, providing a novel strategy for sustainable, high-performance coatings that evolve functionally after application. The intrinsic coating properties were established using PET as an inert model substrate to isolate coating performance from substrate effects. The exceptional barrier and mechanical properties of the developed coating remained effective in preliminary evaluations on paper substrates, confirming its potential for sustainable packaging applications where water resistance and mechanical durability are critical. Copyright © 2026 by Authors, Published by Universitas Diponegoro and BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).